Analisa Pemasaran Digital Pada UMKM Lims Nasi Lemak - Calvin; Julius Kurnaedi; Jimmy Lim; Rano Ardiansyah; Antony Sentoso (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
The development of technology in business is an important factor to increase company productivity. Traditional marketing strategies are no longer effective in the digital age, so it is important to adopt a digital marketing strategy. UMKM Lims Nasi Lemak, which has been operating for 2 years, initially used a simple offline marketing method. However, it is realized that it is necessary to develop a digital marketing strategy. The author recommends using Instagram, Gojek, Grab, and Shopee Food applications  as digital marketing strategies for these MSMEs. The  method used in this study is a qualitative method, where the research is used to analyze and collect data in the form of descriptive and non-numeric. The results of this study are expected that digital marketing strategies can increase the income of MSMEs Lims Nasi Lemak by attracting new customers and retaining old customers. The increased revenue can be used as capital for further marketing, and the presence of MSMEs on these digital platforms will increase efficiency and productivity.